You be you - Kranz, Linda, 1955- (Taylor Trade Pub. : Distributed by National Book Network, 2011)
After exploring his ocean home and seeing many different types of sea life, a young fish named Adri talks to his parents and learns that differences make the world colorful and beautiful.